Patent Wars and Ecosystems: Metaphor and "Black Boxes". Issue 4 (1st October 2016) - Welsh, Joshua
Abstract : Traditionally, the role of metaphor in rhetoric has been seen as recasting the unknown into the realm of the known. Metaphor as explication has been well documented in scholarship of the rhetoric of science. This article argues that scholars interested in the rhetoric of technology should view metaphor as akin to "black boxes." Relying on Lakoff and Johnson's theory of "conceptual metaphor, " it analyzes one episode in the so-called "Smart Phone Patent Wars, " focusing on two metaphors: "ecosystem" and "patent war." Ultimately, the article finds that as black boxes, these metaphors constrain the possible options that people see for their relationships with technology.